A COORDENAÇÃO PEDAGÓGICA COMO ESPAÇO DE FORMAÇÃO CONTINUADA DE PROFESSORES DOS ANOS INICIAIS NO CONTEXTO DO ENSINO DE CIÊNCIAS (Revista Contexto & Educação, 2020)
The present work presents the analysis of an experience of continued training of teachers of the early years focusing on the teaching of science through research. Training activities were proposed in the moments of teachers‘ meeting of the school together with teachers of the initial years. The activities were discussed, organized and then practiced in the classroom with the students and then discussed with the group to prepare a new sequence. From the results we can see that the activities carried out in the teachers‘ meetings of the school in question provided the teachers and the researcher excellent moments of learning and reflection on our teaching practice, enabling us to insert the contents of science in our planning.